Guidelines for water conservation in Brazil - Sousa, Cláudia Orsini Machado de (2023)
In the context of climate change, water related issues become even more problematic, as water availability uncertainties increase. This work seeks to offer subsidies to W&S utilities, local, regional, and national governments, and regulation agencies, for decision-making and strategy development. This dissertation also aims at helping the improvement of public policies and regulations in Brazil, seeking to create resilience, guarantee the availability of water in the country, which is done in four steps: first, evaluating the state of the art of residential water consumption behavior; secondly, assessing if and to what extent the increase in the relevance of private companies in the sanitation market influences residential water saving attitudes; thirdly, identify the main drivers of non-revenue water; and finally, creating a Water Security Index (TWSI), to evaluate water utilities preparedness to extreme water events. For the first step, I developed a structured systematic literature review; for the second and third steps, quantitative research was conducted, using hierarchical linear models; for the fourth step, content analyses combined with scoring technique were used. The results from these four steps show that there is currently a gap between work carried out in developed countries and in developing ones, indicating that most recent and advanced solutions to water management, usually developed in the global north, do not apply to a great part of the nations. The subsidies provided by this dissertation should also help improving the development of public policies and regulations seeking to create resilience and guarantee the availability of water, not only in Brazil, since our conclusions come from the Brazilian perspective, but also for other developing nations, that share similar socio-demographic characteristics. Finally, I include in this work treated data, extracted from SNIS, one of the worlds most complete database on sanitation. Such data may be used for other researchers, as well as policy makers and regulators, in quantitative evaluations and in the field of water and sanitation.